Case study: company analysis Ngopi@Kangar / Ahmad Fahmien Saufi … [et al.] - Saufi, Ahmad Fahmien; Azman, Ameen Azraf; Abd Razak @ Sulimin, Nur Aisyah; Zahari, Siti Anisyah; Aznam, Siti Nur Sarah (2023)
In this case study, we are providing information about the company that we chose, which is Ngopi@Kangar. In our progress doing this report, there is a lot of knowledge that we get in terms of their products and how they manage the business. This is an attempt to understand how the theories learned in this subject can be applied in real-world situations using Business Model Canvas (BMC) and SWOT Analysis. Ngopi@Kangar is the first local cafe in the Northern Region of Malaysia that sells sandwiches and coffee as their main menu. Founded by 100% Bumiputra yet local to Perlis. The name "Ngopi" was inspired by a local language that means "want to have some meals at a cafe or restaurant". The special thing about this cafe is its sandwiches and coffee that serves fresh daily with a marvelous taste. The owner of Ngopi@Kangar is Encik Rizuan and this cafe has run the business for almost 6 years. However, Ngopi@Kangar has its challenges and problems in the business. The major problems are the small range of the products and the delivery services provided. To ensure that they can retain their customers, the business can play a big role. In conclusion, the selection of Ngopi@Kangar as the subject of the case study helped to achieve an effective business strategy for production. They have shown that they can succeed in this business and have developed quite a reputation. We also recommend some ways for this cafe or any organization to practice improving for their business success.